2000
DOI: 10.1177/0145482x0009400505
|View full text |Cite
|
Sign up to set email alerts
|

A National Outcomes Assessment of the Rehabilitation of Adults with Visual Impairments

Abstract: This article discusses the development of self-report functional outcomes instruments in two years of a three-year large-scale national research project on the rehabilitation of adults with visual impairments. It describes the history of the effort, the process involved, and the methods used in establishing the instruments’ reliability, validity, and responsivity and the results of intermediate analyses of the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 2 publications
0
23
0
Order By: Relevance
“…In evaluating the benefits and effectiveness of guide dog ownership, the assessed variables might include the dog's breed, training, and characteristics as well as demographic and situational factors relating to the owner. Measuring the impact of services in relation to visually impaired users' needs is beginning to be integrated into rehabilitation and mobility service provision in general (see, e.g., De l'Aune et al 74 ), but the particular impact and efficacy of guide dogs has been given comparatively little attention.…”
Section: Limitations Of the Study And Areas For Further Researchmentioning
confidence: 99%
“…In evaluating the benefits and effectiveness of guide dog ownership, the assessed variables might include the dog's breed, training, and characteristics as well as demographic and situational factors relating to the owner. Measuring the impact of services in relation to visually impaired users' needs is beginning to be integrated into rehabilitation and mobility service provision in general (see, e.g., De l'Aune et al 74 ), but the particular impact and efficacy of guide dogs has been given comparatively little attention.…”
Section: Limitations Of the Study And Areas For Further Researchmentioning
confidence: 99%
“…The results for the plus intersection showed a significant main effect of fixation category (i.e., vehicles, crossing elements, traffic controls) (F [2,19] ϭ 62.58, p Ͻ 0.0001). The interaction between phase and category was also significant (F [4,17] ϭ 37.37, p Ͻ 0.0001).…”
Section: Resultsmentioning
confidence: 94%
“…In a sample of 759 visually impaired veterans, only 37% reported crossing the street on a daily or weekly basis before rehabilitation. 2 Geruschat et al 3 evaluated the gaze behavior of fully sighted subjects crossing streets and found that the subjects allocated their fixations on task-relevant features of the environment, which were crossing elements, vehicles, and traffic controls. The finding that fully sighted subjects fixate on taskrelevant features while walking has been reported previously.…”
mentioning
confidence: 99%
“…However, in a study of 200 visually impaired veterans in 1995, Atlanta Veterans Affairs investigators found that 60 percent of the veterans were using only approximately 40 percent of their assistive devices a year after they had received them. 4 In a 1999 national survey on veteran satisfaction with VA rehabilitation services, the Atlanta VA investigators discovered the reason for such disuse. 4 They asked visually impaired veterans about their ability to independently perform such basic tasks as paying their bills and balancing their checkbooks.…”
Section: The Changing Needs Of the Disabledmentioning
confidence: 99%